Association between urine uranium and asthma prevalence - Dongdong Huang; Saibin Wang (Frontiers Media S.A., 2024)
BackgroundPrevious studies showed that urine uranium (U) is associated with asthma prevalence in adults. However, the association between them among the general population is unclear. Therefore, this study aimed to explore this unclear association.MethodsThe data of the participants were collected from the 2007-2016 National Health and Nutrition Examination Survey (NHANES) performed in the United States. Continuous variables with a skewed distribution were analyzed using Ln-transformation. The association between urine U and asthma prevalence was analyzed by multiple regression analysis, and the linear association between them was evaluated by smoothed curve fitting. The subgroup analysis was performed using the hierarchical multivariate regression analysis.ResultsA total of 13,581 participants were included in our analysis. The multivariate regression analysis showed that LnU was independently and positively correlated with asthma prevalence in the general population (OR = 1.12; 95% CI: 1.04-1.20; p = 0.002). The subgroup analysis revealed that college graduate or above showed a stronger association between LnU and asthma prevalence (<9th grade: OR = 0.84; 95% CI: 0.61-1.14; 9-11th grade: OR = 1.23; 95% CI: 0.99-1.52; high school grade: OR = 1.00; 95% CI: 0.84-1.19; college: OR = 1.04; 95% CI: 0.91-1.19; ≥college graduate: OR = 1.32; 95% CI: 1.11-1.57; P for interaction = 0.0389).ConclusionOur research suggested that urinary U levels are positively associated with asthma prevalence among the general population of the United States, and the association is especially strong among people with high levels of education.